FROM SOVIET INTERVENTION TO THE ESTABLISHMENT OF COOPERATION WITH NATO: THE EVOLUTION OF INTERNATIONAL RELATIONS IN EASTERN EUROPE IN 1945-1991 - Illia Butenko (The Journal of V. N. Karazin Kharkov National University. Issues of Political Science, 2024)
The article examines the mechanisms of Soviet influence on the policies of Central and Eastern European states during the Cold War in the context of the processes of changing the vision of the countries of the region in relations with the USSR and the North Atlantic Alliance (NATO). The article analyzes the cases of Soviet military intervention in the politics of the socialist bloc states in 1953, 1956 and 1968, as well as the policy of détente in international relations and the fall of communist regimes in the context of changes in the foreign policy of Central and Eastern European countries. The research interest is aimed at identifying the main factors of transformation of international relations in Central and Eastern Europe during the Cold War. The author defines the geopolitical situation in the region as a policy of limiting the sovereignty of countries by the USSR. Attention is paid to the processes of creating conditions for changing the balance of power in the region. According to the results of the study, it is noted that the process of changing the vision of the foreign policy course of the countries of Central and Eastern Europe was influenced by such factors as the precedents of the USSR's military intervention in the policies of the Warsaw Pact (WP) member states, the formation of a trend towards building relations between the countries of the region and the states of Western Europe in the 1970s, and the existence of an image of a more flexible and mutually beneficial model of international security cooperation in the form of the Euro-Atlantic partnership within NATO. It is noted that the change in the situation in the field of international relations in the region was influenced by the fall of the communist regimes in Central and Eastern Europe in the late 1980s and the formation of new elites who considered the establishment of relations with NATO as a foreign policy priority for the countries of the region.